Use of covid-19 convalescent plasma to treat patients admitted to hospital for covid-19 with or without underlying immunodeficiency: open label, randomised clinical trial - Arsène Mekinian; Xavier Mariette; Florence Ader; Raphaël Porcher; Philippe Ravaud; Lionel Piroth; Gabriel Baron; Jean-Marie Michot; Karine Lacombe; Tabassome Simon; Sophie Georgin-Lavialle; Charles Cazanave; et al. (BMJ Medicine)
Objective To evaluate the efficacy of covid-19 convalescent plasma to treat patients admitted to hospital for moderate covid-19 disease with or without underlying immunodeficiency (CORIPLASM trial).Design Open label, randomised clinical trial.Setting CORIMUNO-19 cohort (publicly supported platform of open label, randomised controlled trials of immune modulatory drugs in patients admitted to hospital with moderate or severe covid-19 disease) based on 19 university and general hospitals across France, from 16 April 2020 to 21 April 2021.Participants 120 adults (n=60 in the covid-19 convalescent plasma group, n=60 in the usual care group) admitted to hospital with a positive SARS-CoV2 test result, duration of symptoms <9 days, and World Health Organization score of 4 or 5. 49 patients (n=22, n=27) had underlying immunosuppression.Interventions Open label randomisation to usual care or four units (200-220 mL/unit, 2 units/day over two consecutive days) of covid-19 convalescent plasma with a seroneutralisation titre >40.Main outcome measures Primary outcomes were proportion of patients with a WHO Clinical Progression Scale score of ≥6 on the 10 point scale on day 4 (higher values indicate a worse outcome), and survival without assisted ventilation or additional immunomodulatory treatment by day 14. Secondary outcomes were changes in WHO Clinical Progression Scale scores, overall survival, time to discharge, and time to end of dependence on oxygen supply. Predefined subgroups analyses included immunosuppression status, duration of symptoms before randomisation, and use of steroids.Results 120 patients were recruited and assigned to covid-19 convalescent plasma (n=60) or usual care (n=60), including 22 (covid-19 convalescent plasma) and 27 (usual care) patients who were immunocompromised. 13 (22%) patients who received convalescent plasma had a WHO Clinical Progression Scale score of ≥6 at day 4 versus eight (13%) patients who received usual care (adjusted odds ratio 1.88, 95% credible interval 0.71 to 5.24). By day 14, 19 (31.6%) patients in the convalescent plasma group and 20 (33.3%) patients in the usual care group needed ventilation, additional immunomodulatory treatment, or had died. For cumulative incidence of death, three (5%) patients in the convalescent plasma group and eight (13%) in the usual care group died by day 14 (adjusted hazard ratio 0.40, 95% confidence interval 0.10 to 1.53), and seven (12%) patients in the convalescent plasma group and 12 (20%) in the usual care group by day 28 (adjusted hazard ratio 0.51, 0.20 to 1.32). In a subgroup analysis performed in patients who were immunocompromised, transfusion of covid-19 convalescent plasma was associated with mortality (hazard ratio 0.39, 95% confidence interval 0.14 to 1.10).Conclusions In this study, covid-19 convalescent plasma did not improve early outcomes in patients with moderate covid-19 disease. The efficacy of convalescent plasma in patients who are immunocompromised should be investigated further.Trial registration ClinicalTrials.gov NCT04345991.